Ovarian Stimulation in Patient-oriented Strategies Encompassing Individualised Oocyte Number-4 Category; Antagonist versus Short-agonist Protocols - Tarek K. Al-Hussaini; Ahmed Aboelfadle Mohamed; Ayman Askar; Ahmed A. Abden; Yousra M. Othman; Reda S. Hussein (Journal of Human Reproductive Sciences)
Background: Recently POSEIDON (Patient-Oriented Strategies Encompassing Individualized Oocyte Number) classification was proposed to categorize patients with expected poor response to conventional stimulation. Searching for the ideal management of poor responders in IVF is still an active research area. Aims: This study compares GnRH-antagonist and GnRH-agonist short protocols in ICSI cycles for the POSEIDON-4 group. Settings and Design: This retrospective study was conducted in a tertiary infertility unit between January 2016 and December 2020. Materials and Methods: Infertile women who met the criteria for POSEIDON 4 group and underwent fresh ICSI-ET in using GnRH-antagonist and GnRH-agonist short protocols was performed. POSEIDON-4 includes patients ≥ 35 years with poor ovarian reserve markers; AFC < 5 and AMH < 1.2 ng/ml. Statistical Analysis Used: Numerical variables were compared between both groups by student’s t test and Mann Whitney test when appropriate. Chi-square test used to compare categorical variables. Multivariate logistic regression models were utilized to adjust for the effect of the different study confounders on live birth rate. Results: One hundred ninety fresh ICSI cycles were analyzed. Of the total cohort, 41.6 % (79) patients pursued antagonist protocol compared to 58.4% (111) underwent short agonist protocol. Fresh embryo transfer was accomplished in 55.7 % (44/79) vs. 61.3 % (68/111), P = 0.44 in antagonist vs. short protocol respectively. Cycle cancellation due to poor ovarian response was encountered in (32.9%vs. 27.9%, P = 0.50) in the antagonist and short groups, whereas no good-quality embryos were developed after ovum pickup in 11.4% vs. 10.8%, P>0.05. Comparable total gonadotropins dose, number of retrieved and mature oocytes, and good-quality embryos were found in both groups. Likewise, clinical pregnancy rate was not different for the antagonist and short groups [11/79 (13.9%) vs. 20/111 (18%), P = 0.45]. The live birth rate was comparable between both groups (8.9% vs. 10.8%, P = 0.659) for antagonist and short groups respectively. No significant impact for the protocol type on live birth rate was revealed after adjusting to cycle confounders in multivariate analysis (OR: 0.439, 95%CI 0.134-1.434, P = 0.173). Conclusion: This study shows comparable pregnancy outcomes for antagonist and short-agonist protocols in IVF/ICSI cycles for POSEIDON-4 category.